Prevalence of the crayfish plague pathogen Aphanomyces astaci in populations of the signal crayfish Pacifastacus leniusculus in France: evaluating the threat to native crayfish - Filipová, Lenka; Petrusek, Adam; Matasová, Klára; Delaunay, Carine; Grandjean, Frédéric (PloS one, 2013)
Aphanomyces astaci, the crayfish plague pathogen, first appeared in Europe in the mid-19(th) century and is still responsible for mass mortalities of native European crayfish. The spread of this parasite across the continent is especially facilitated by invasive North American crayfish species that serve as its reservoir. In France, multiple cases of native crayfish mortalities have been suggested to be connected with the presence of the signal crayfish Pacifastacus leniusculus, which is highly abundant in the country. It shares similar habitats as the native white-clawed crayfish Austropotamobius pallipes and, when infected, the signal crayfish might therefore easily transmit the pathogen to the native species. We investigated the prevalence of A. astaci in French signal crayfish populations to evaluate the danger they represent to local populations of native crayfish. Over 500 individuals of Pacifastacus leniusculus from 45 French populations were analysed, plus several additional individuals of other non-indigenous crayfish species Orconectes limosus, O. immunis and Procambarus clarkii. Altogether, 20% of analysed signal crayfish tested positive for Aphanomyces astaci, and the pathogen was detected in more than half of the studied populations. Local prevalence varied significantly, ranging from 0% up to 80%, but wide confidence intervals suggest that the number of populations infected by A. astaci may be even higher than our results show. Analysis of several individuals of other introduced species revealed infections among two of these, O. immunis and P. clarkii. Our results confirm that the widespread signal crayfish serves as a key reservoir of Aphanomyces astaci in France and therefore represents a serious danger to native crayfish species, especially the white-clawed crayfish. The prevalence in other non-indigenous crayfish should also be investigated as they likely contribute to pathogen transmission in the country.
Keywords: Aphanomyces; France; Animals; Astacoidea; Real-Time Polymerase Chain Reaction; DNA řas; zvířata; DNA, Algal; Francie; kvantitativní polymerázová řetězová reakce; severní raci